HIV/AIDS, Household Income, and Consumption Dynamics in Malawi - Masanjala, Winford H. (International Food Policy Research Institute, 2006)
A survey of recent writings on the interactions between the AIDS epidemic and livelihoods in Africa leaves one with the impression that development practitioners, academics, and even casual observers of developments in Africa are hell-bent on pinning most of Africa’s economic stagnation on the AIDS epidemic. This is all the more troubling because, although in the past 15 years economists have attempted to systematically link AIDS and poverty and to test the strength of those linkages, the relationships among livelihoods, poverty, and the AIDS epidemic remains so complex that we still know little about the actual contribution of AIDS in explaining observed cases of persistent poverty and divergent economic fortunes in Africa. For instance, a number of macro-level forecasts, from the pioneering studies (Ainsworth and Over 1992; Cuddington 1993; Cuddington and Hancock 1994) to more recent ones (e.g., Bloom and Mahal 1997; Greener, Jefferis, and Siphambe 2000; Arndt and Lewis 2001; Haacker 2002; Crafts and Haacker 2003) have generated an almost universal consensus that the AIDS epidemic will have an immense impact on the macroeconomies of hard-hit countries, significantly slowing economic growth and worsening poverty and income distribution (also see summaries in UNFPA 2002; UNAIDS 2002). Yet recent experience seems to suggest that because the HIV population is still a relatively small proportion of the total population, even in hard-hit countries, macro-level economic impacts of AIDS are likely to be barely visible in national statistics (Desbarats 2002).